2018
DOI: 10.1016/j.bone.2018.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Removal of matrix-bound zoledronate prevents post-extraction osteonecrosis of the jaw by rescuing osteoclast function

Abstract: Unlike other antiresorptive medications, bisphosphonate molecules accumulate in the bone matrix. Previous studies of side-effects of anti-resorptive treatment focused mainly on systemic effects. We hypothesize that matrix-bound bisphosphonate molecules contribute to the pathogenesis of bisphosphonate-related osteonecrosis of the jaw (BRONJ). In this study, we examined the effect of matrix-bound bisphosphonates on osteoclast differentiation in vitro using TRAP staining and resorption assay, with and without pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
2
18
1
Order By: Relevance
“…Oral swabs showed an increase in bacterial 16s rRNA expression (P = .0023; Figure 1A). Consistent with our previous studies, 5,23 Zol-treated animals showed exposed necrotic bone, persistent for 8 weeks after extraction, compared with complete healing and mucosal coverage in control animals ( Figure 1B). To study the effect of Zol on DC activity, isolation of cervical lymph nodes was performed at 2 weeks, and harvest of mandibles and gingival tissues at 8 weeks following extraction.…”
Section: Impaired DC Activity and Increased Oral Bacterial Load In supporting
confidence: 92%
See 2 more Smart Citations
“…Oral swabs showed an increase in bacterial 16s rRNA expression (P = .0023; Figure 1A). Consistent with our previous studies, 5,23 Zol-treated animals showed exposed necrotic bone, persistent for 8 weeks after extraction, compared with complete healing and mucosal coverage in control animals ( Figure 1B). To study the effect of Zol on DC activity, isolation of cervical lymph nodes was performed at 2 weeks, and harvest of mandibles and gingival tissues at 8 weeks following extraction.…”
Section: Impaired DC Activity and Increased Oral Bacterial Load In supporting
confidence: 92%
“…Zol is known to have the highest affinity to the bone matrix, where it accumulates for years . We previously showed that matrix‐bound Zol molecules play an important role in making the alveolar bone susceptible to osteonecrosis . However, the question remained as to why other bone sites that have similarly high levels of matrix‐bound Zol, such as the proximal end of the tibia, are not comparably vulnerable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have observed that TRAP-positive cells decrease in the MRONJ model [41]. In contrast, TRAP-positive cells increased in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…An increasing body of evidence suggests that ZA inhibits the differentiation of osteoclasts in vitro through various pathways, including inhibition of receptor activator of nuclear factor κB ligand (RANKL)/receptor activator of nuclear factor κB (RANK) pathway, non-canonical Wnt/Ca 2+ /calmodulin dependent protein kinase II (CaMKII) pathway, and prevention of macrophage differentiation into osteoclasts [ 19 , 25 , 26 ].…”
Section: Inhibition Of Differentiation Of Osteoclasts By Zamentioning
confidence: 99%